Wireless Sensors in Industrial Time-Critical Environments - Cecílio, José.; Furtado, Pedro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Modern industrial systems are often highly automated, with hundreds or even thousands of sensors and actuators monitoring the various processes, overseen by a distributed control system (DCS). Such control systems increasingly make use of wireless communications, yet these must still satisfy all safety-critical requirements. This unique text introduces the components, operations, industry protocols and standards of DCS, and shows how to include wireless technology in their design while guaranteeing the desired operation characteristics. The book not only discusses the theory, but also presents insights and results gained from extensive practical experience in implementing and testing systems within a specific industrial setting. Topics and features: Reviews the concepts, components and architectures supporting DCS Examines the operations that the DCS implements, covering human-machine interfaces, diagnostics and maintenance interfaces, and controllers Discusses industrial control system and wireless network protocols Reviews scheduling in wireless sensor networks Describes a latency model for heterogeneous DCS with wired and wireless parts, that predicts monitoring latencies, command latencies and closed loop latencies Explains how to plan operation timings systematically Introduces measures and metrics for performance monitoring and debugging, and describes how to add performance monitoring and debugging to a system Presents experimental results to validate the planning approach, based on an application test-bed This practical guide for real-world implementation will be of considerable interest to a wide audience, from professional engineers to researchers and students. It is suitable as a supporting text for courses covering industrial systems, networks, real-time systems, wireless sensor networks or embedded systems.
Introduction -- Industrial Control Systems: Concepts, Components and Architectures -- Distributed Control System Operations -- Industrial Protocols and Planning Considerations -- Scheduling of Wireless Sensor Networks -- Latency Modeling for Distributed Control Systems with Wired and Wireless Sensors -- Planning for Distributed Control Systems with Wired and Wireless Sensors -- Performance and Debugging -- Application Scenario: An Industrial Case Study -- Network Configuration: Example -- Network Layout: Example -- Evaluation of Planning and Monitoring Approaches: Details.
Keywords: Computer communication systems; Control engineering; Computer Communication Networks; Control and Systems Theory